2016
DOI: 10.1063/1.4948538
|View full text |Cite
|
Sign up to set email alerts
|

Superlattice gain in positive differential conductivity region

Abstract: We analyze theoretically a superlattice structure proposed by A. Andronov et al. [JETP Lett 102, 207 (2015)] to give Terahertz gain for an operation point with positive differential conductivity. Here we confirm the existence of gain and show that an optimized structure displays gain above 20 cm −1 at low temperatures, so that lasing may be observable. Comparing a variety of simulations, this gain is found to be strongly affected by elastic scattering. It is shown that the dephasing modifies the nature of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Multiperiod SLs are the prime candidates for this job because they have all the components required for light amplification and their designs seems to be simpler and more reliable, than designs of quantum cascade lasers (QCLs) [8,9] . The ongoing simplification of designs of QCLs towards the SLs [10,11] confirms this conclusion.…”
Section: Introductionsupporting
confidence: 56%
“…Multiperiod SLs are the prime candidates for this job because they have all the components required for light amplification and their designs seems to be simpler and more reliable, than designs of quantum cascade lasers (QCLs) [8,9] . The ongoing simplification of designs of QCLs towards the SLs [10,11] confirms this conclusion.…”
Section: Introductionsupporting
confidence: 56%
“…3,12) It has been reported that the interminiband Zener tunneling 3,[18][19][20][21][22] of electrons can be used as a key concept to prevent the formation of field domains and also coexist with tunable terahertz gain in doped narrow-minigap SLs, where the first miniband mixes substantially with higher minibands in the conduction band under bias field. [23][24][25][26][27] Very recently, we have discovered peculiar Bloch oscillations as well as interminiband Zener tunneling in an undoped narrowminigap SL excited by femtosecond optical pulses at low temperatures of  T 80 K: the oscillation phase has a π/2 shift induced by interminiband mixing 28) and the dephasing time has a characteristic dependence on the excitation photon energy as explained by the miniband transport model, 29) in contrast to the Bloch oscillations reported for ordinary SLs with nearly isolated minibands. 14,15) However, the detailed properties of interminiband Zener tunneling, including its coexistence with Bloch oscillations at such temperatures that thermal energy kT (k: Boltzmann constant) exceeds the relevant minigap, have not yet been understood.…”
mentioning
confidence: 94%
“…By using the Kronig-Penney model, we estimated that the first miniband in the conduction band had a width of 14.8 meV, the second miniband had a width of 47.9 meV, and they were separated by a minigap as narrow as 8.4 meV. [23][24][25][26][27][28] Under dc bias voltages applied between the front and back surfaces of the sample at 80 K, electrons were excited near the bottom of the conduction first miniband by optical pulses (with a duration of ∼100 fs) delivered from a mode-locked Ti: sapphire oscillator. The electron density was kept as low as ∼2 × 10 14 cm −3 to minimize the field screening effect and the dynamic depolarization effect.…”
mentioning
confidence: 99%